2020
DOI: 10.1016/j.corsci.2020.108738
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of microstructure and electrical performance in doped Mn-Co and Cu-Mn oxide layers with the extended oxidation time

Abstract: Mn-Co and Cu-Mn based alloy coatings are deposited on 430 SS by high energy micro-arc alloying process, and then alloy coatings are oxidized at 750 ℃ in air to form the spinel oxides. Some composite oxides, such as Co3O4, Mn2O3 and (Mn,Co)3O4, are formed at the initial stage of oxidation. The single-phase spinel (pure MnCo2O4) without impurity phases is only found on the surface of Co-33Mn-17Cu oxide layer with the extended oxidation time, its area-specific resistance values at 500 ℃ to 800 ℃ are low and close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Ti alloys of α-type and α + β type are frequently used in early biomedical applications. The application environment, alloy compositions, and microstructure are typically important determinants of how corrosion behaves in metallic materials [133][134][135]. The environment inside the human body, for instance during inflammation and allergies, is typically steady, despite the fact that human temperature, environmental chemistry, and pH might occasionally change.…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…Ti alloys of α-type and α + β type are frequently used in early biomedical applications. The application environment, alloy compositions, and microstructure are typically important determinants of how corrosion behaves in metallic materials [133][134][135]. The environment inside the human body, for instance during inflammation and allergies, is typically steady, despite the fact that human temperature, environmental chemistry, and pH might occasionally change.…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…Powder metallurgy (PM) uses the powder of pure metals, blends, or alloys as raw materials, and it produces metallic parts by forming and/or sintering [125][126][127][128][129][130]. Before the process of PM, the powder would be compressed in a mold, which aims to attain the required shapes and dimensions of the model [23,125,[131][132][133].…”
Section: Powder Metallurgymentioning
confidence: 99%
“…In the early stage, α-type and α + β-type Ti alloys are commonly applied for biomedical applications. Generally, the corrosion behavior of metallic materials depends on several factors: applied environment, alloy compositions, and microstructure [127,[211][212][213][214]. The human body has a relatively stable environment, while human temperature, environmental chemistry, and pH would change in some cases (e.g., inflammation and allergy).…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…The composition is a fundamental factor determining the corrosion resistance of metallic materials [1][2][3][4][5][6][7]. To understand the corrosion mechanism and enhance the corrosion resistance of metals, tremendous effects have been done based on the principle of composition controlling [1,4,8,9]. It is revealed that the corrosion resistance of alloys is mainly impacted by the type and concentration of the elements [1][2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%